Inhomogeneous screening of gate electric field by interface states in graphene FETs. (17th August 2017) - Singh, Anil Kumar; Gupta, Anjan Kumar
Abstract: The electronic states at graphene-SiO2 interface and their inhomogeneity is investigated using the back-gate-voltage dependence of local tunnel spectra acquired with a scanning tunneling microscope. The conductance spectra show two, or occasionally three, minima that evolve along the bias-voltage axis with the back gate voltage. This evolution is modeled using tip-gating and interface states. The energy dependent interface states' density, D i t ( E ), required to model the back-gate evolution of the minima, is found to have significant inhomogeneity in its energy-width. A broad D i t ( E ) leads to an effect similar to a reduction in the Fermi velocity while the narrow D i t ( E ) leads to the pinning of the Fermi energy close to the Dirac point, as observed in some places, due to enhanced screening of the gate electric field by the narrow D i t ( E ) . Finally, this also demonstrates STM as a tool to probe the density of interface states in various 2D Dirac materials.